A Rare Complication of Hyperplastic Gastric Polyp. (20th January 2013) - Nayudu, Suresh Kumar; Niazi, Masooma; Balar, Bhavna; Kumbum, Kavitha
Abstract : Hyperplastic gastric polyps are incidentally diagnosed during upper gastrointestinal endoscopy. They are known to cause gastric outlet obstruction and chronic blood loss leading to iron deficiency anemia. However, hyperplastic gastric polyp presenting as acute severe upper gastrointestinal bleeding is very rare. To the best of our knowledge, there have been two cases of hyperplastic gastric polyps presenting as acute gastrointestinal bleeding in the medical literature. We present a case of a 56-year-old African American woman who was admitted to our hospital with symptomatic anemia and sepsis. The patient developed acute upper gastrointestinal bleeding during her hospital stay. She underwent emergent endoscopy, but bleeding could not be controlled. She underwent emergent laparotomy and wedge resection to control the bleeding. Biopsy of surgical specimen was reported as hyperplastic gastric polyp. We recommend that physicians should be aware of this rare serious complication of hyperplastic gastric polyps as endoscopic polypectomy has diagnostic and therapeutic benefits in preventing future complications including bleeding.